Urban (in) security in an emerging human settlement: Perspectives from Hopley Farm Settlement, Harare, Zimbabwe - Matamanda, Abraham R.; Mphambukeli, Thulisile N. (Frontiers in Sustainable Cities, 2022)
This article examines the urban (in) security landscape in a postcolonial emerging human settlement in Africa. Hopley Farm settlement is used as a case study focusing on the perspectives of this urban (in) security on spatial justice. This study is significant and timely. It contributes to the emerging scholarship on African cities that focuses on urban security, which is increasingly becoming a critical issue owing to multiple socio-economic, political, and environmental risks inherent in Africa. The poor residing in emerging human settlements are victimized mainly and subjected to different forms of violence that expose them to urban (in) securities making it challenging to achieve the envisaged sustainable development goal that aspires to create safe and resilient cities and settlements by 2030. The study employed an exploratory phenomenological research design where data were collected from 450 questionnaires administered to residents and 20 in depth interviews with residents from Hopley. Thematic analysis was used to analyse the data. The study maps Hopley's (in) security terrain, focusing on the nature and severity. The strategies employed by the community to navigate this complex terrain is explored in light of spatial justice. The findings reveal that the envisaged mixed used settlement form considers urban security in the design of Hopley. However, the realities of the settlement show multiple urban insecurities that are complex and include unsafe living environments, political victimization, lack of tenure, crime and violence. Spatial injustice is thus prevalent in this community and calls for the government to reconsider the planning, development and management of emerging settlements where the poor reside in the shadow of the state.